Factors Influencing Mothers in Breastfeeding in Sibolahotang SAS Village, Balige District, Toba Regency, Year 2025 - Munarni Simatupang; Erita Saragih (International Journal Of Health Science, 2025)
This study aims to identify and analyze the factors influencing mothers in providing breast milk (ASI) to infants aged 0–24 months in Sibolahotang SAS Village, Balige District, Toba Regency. Breastfeeding is a crucial determinant of infant health and development, yet many mothers face challenges that affect exclusive breastfeeding practices. The research employed a descriptive quantitative method with 56 respondents selected using total sampling. Data were collected through structured questionnaires and analyzed descriptively to determine the level of support and knowledge influencing breastfeeding. The results showed that most respondents (71.4%) were unemployed, and 78.6% received breastfeeding information from health workers. All respondents (100%) reported supportive roles from fathers and families in the breastfeeding process, while 87.5% acknowledged support from healthcare providers. Additionally, all mothers (100%) demonstrated good knowledge about the benefits and importance of breastfeeding. These findings highlight that social support and adequate knowledge are key factors contributing to the success of breastfeeding. Strengthening educational interventions and involving family members, especially fathers, in breastfeeding programs are essential strategies to improve maternal and child health outcomes. This research contributes to the understanding of community-based breastfeeding promotion and provides a foundation for future studies and policy formulation related to maternal and child health development in Indonesia.